Tissue-resident and innate-like T cells in patients with advanced chronic liver diseaseKey points - Oluwatomi Ibidapo-Obe; Tony Bruns (JHEP Reports, 2023)
Summary: Chronic liver disease results from the orchestrated interplay of components of innate and adaptive immunity in response to liver tissue damage. Recruitment, positioning, and activation of immune cells can contribute to hepatic cell death, inflammation, and fibrogenesis. With disease progression and increasing portal pressure, repeated translocation of bacterial components from the intestinal lumen through the epithelial and vascular barriers leads to persistent mucosal, hepatic, and systemic inflammation which contributes to tissue damage, immune dysfunction, and microbial infection. It is increasingly recognised that innate-like and adaptive T-cell subsets located in the liver, mucosal surfaces, and body cavities play a critical role in the progression of advanced liver disease and inflammatory complications of cirrhosis. Mucosal-associated invariant T cells, natural killer T cells, γδ T cells, and tissue-resident memory T cells in the gut, liver, and ascitic fluid share certain characteristic features, which include that they recognise microbial products, tissue alarmins, cytokines, and stress ligands in tissues, and perform effector functions in chronic liver disease. This review highlights recent advances in the comprehension of human tissue-resident and unconventional T-cell populations and discusses the mechanisms by which they contribute to inflammation, fibrosis, immunosuppression, and antimicrobial surveillance in patients with cirrhosis. Understanding the complex interactions of immune cells in different compartments and their contribution to disease progression will provide further insights for effective diagnostic interventions and novel immunomodulatory strategies in patients with advanced chronic liver disease.